The illusion of luxury: Augmented reality's clash with brand essence - Lucas Nann; David Finken; Tim Döring; Reto Hofstetter (Marketing Review St.Gallen, 2024)
Many luxury brands have ventured into the virtual realm (e.g., metaverse, AR product displays) to showcase their products. However, prior research has failed to empirically test how virtuality affects luxury brand perceptions. Because the fundamental nature of luxury brands (i.e., high quality, exclusivity, prestige, and authenticity) contradicts the characteristics of AR, adverse effects could occur. This research presents two studies demonstrating that displaying luxury products in AR diminishes the brand essence of the focal brand, resulting in a reduction of brand authenticity.
Keywords: 650